Internet commerce: problems and prospects for development in Ukraine (Economics and region, 2023)
The steady and rather rapid development of e-commerce over the past decade has become one of the most visible changes in society. Today, there are many domestic and foreign online stores in Ukraine, which allows consumers to have a wide choice and find the best price for the right product. Today, e-commerce in Ukraine is quite developed and has a good potential for further growth, solving many problems that were inherent in retail trade, but creating new ones that require attention. The article presents and analyzes the main indicators characterizing the current state of the e-commerce market and draws conclusions. The main problems of domestic e-commerce are identified and characterized. The main problems in our country that slow down the development of Internet business are: not very high paying capacity and living standards, low development of the legislative framework, insufficient level of computer literacy, introduction of innovative payment methods, etc. There are also problems in building and using a high-quality management system, certain elements of the accounting system, documentation and taxation of online stores. The article considers advantages, disadvantages, weaknesses and strengths using the SWOT analysis of Internet business and offers some recommendations for its improvement. Having considered the advantages and disadvantages of e-commerce in our country, the article offers a number of recommendations that will help to increase the level of e-commerce in Ukraine. The main directions of stimulating the development of e-commerce can be considered the harmonization of legal norms, ensuring legal protection of e-commerce entities, removing barriers to the development of international e-business, and building the infrastructure of the e-commerce market. The article will be useful for specialists in the field of Internet marketing, entrepreneurs, economists and scientists engaged in market demand research, teachers and students of higher education institutions.
Keywords: Internet commerce; e-commerce; e-trade; problems; goods